A Case of Breathlessness during Pregnancy: The Difficulty in Diagnosing Heart Failure. (March 2013) - Snow, Timothy A C; Wasywich, Cara A; Stewart, Fiona M
We present the case of a 33-year-old woman in her second pregnancy who was transferred to our unit following a one-month history of worsening fatigue and a three-day history of worsening symptoms of heart failure. Shortly after presentation she developed ventricular fibrillation and arrested. At an emergency caesarean section a placental abruption was noted and the baby was stillborn, unable to be resuscitated. The patient required a prolonged intensive and coronary care stay. Echocardiographic findings were consistent with dilated cardiomyopathy and as all investigations to ascertain a cause were negative she was diagnosed with peripartum cardiomyopathy. Her case highlights a potential fatal cause of breathlessness during pregnancy and the role of B-type natriuretic peptide to assist in the differential diagnosis of these cases.